State-of-the-Art Biosensors in China - Yu, Ping (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Every new development in biosensors matters to the global sensor market and burgeoning field of interdisciplinary research that is hailed as a potential revolution in healthcare, consumer and industrial testing. The goal/objective of this Special Issue is to keep scholars, inspection agencies and companies informed on the progress of research into state-of-the-art biosensors in China. Specifically, this Special Issue serves as a means of showing that the biosensors have been proven at the concept level and developed in the laboratory setting; thus, many sensors could have strong healthcare or commercial applications.